A REVIEW ON ISSUES ASSOCIATED WITH THE SHELTER RECONSTRUCTION AFTER GORKHA EARTHQUAKE 2015 IN NEPAL - Dhungana, Anoj; Dahal, Khet Raj; Shrestha, Subik; Thapa, Narbikram; Neupane, Sanchita (International Journal of Research -GRANTHAALAYAH, 2017)
A study on “Issues associated with the shelter reconstruction after Gorkha Earthquake 2015 in Nepal” was conducted during the period of March to September 2017 on the basis of secondary literature received from different sources and field observation. Various articles, journal and government documents retrieved from online research database like ‘Google Scholars’ and topic related government online sites were reviewed. It has been realized that reconstruction after disasters is a long process. To manifest and implement the notion of build back better and successful completion of shelter reconstruction projects, there is a need for an in-depth knowledge of construction project management because 600,000 houses are to be constructed and about 250,000 to be repaired and retrofitted as well. The study reveals that the lack of funding, construction materials, labors and experienced human resources hinder the smooth progress of reconstruction. Similarly, reconstruction projects can take place only when the affected people are also involved in the design and planning process as well as in the implementation phase of the project, ensuring the best utilization of local knowledge and resources as much as possible. The strong coordination among various stakeholders can act as the key to an effective reconstruction in the context of Nepal.